Exploring microstructural changes in structural analogues of ibuprofen-hosted in situ gelling system and its influence on pharmaceutical performance - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (AAPS Pharmscitech, 2015)
The present work explores inner structuration of in situ gelling system consisting of glyceryl monooleate (GMO) and oleic acid (OA). The system under study involves investigation of microstructural changes which are believed to govern the pharmaceutical performance of final formulation. The changes which are often termed mesophasic transformation were analysed by small angle Xray scattering (SAXS), differential scanning calorimetry (DSC), rheology and plane polarised light (PPL) microscopy. The current work revealed transformation of blank system from W/O emulsion to reverse hexagonal structure upon addition of structural analogues of ibuprofen. Such transformations are believed to occur due to increased hydrophobic volume within system as probed by SAXS analysis. The findings of SAXS studies were well supported by DSC, rheology and PPL microscopy. The study established inverse relationship between log P value of structural analogues of ibuprofen and the degree of binding of water molecules to surfactant chains. Such relationship had pronounced effect on sol-gel transformation process. The prepared in situ gelling system showed sustained drug release which followed Higuchi model.
Keywords: flurbiprofen; hexagonal phase; ibuprofen; ketoprofen; liquid crystal; sustained drug release